2015
DOI: 10.1186/s12879-015-0881-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term spontaneous fluctuations of HBV DNA levels in a Senegalese population with chronic hepatitis B

Abstract: BackgroundWe evaluated the short-term spontaneous fluctuations of HBV DNA and HBsAg levels in Senegalese patients with chronic infection with hepatitis B virus and normal ALT and determined factors related to these fluctuations.MethodA total of 87 patients with persistent normal ALT values were enrolled in the study. Serum samples were obtained at three different visits, with an interval of 2 months (M0, M2, and M4), and without initiating anti HBV treatment. Levels of HBV DNA, quantitative HBsAg, ALT and AST,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 23 publications
9
14
0
Order By: Relevance
“…This is in concordance with a Turkish study, which demonstrated that mean qHBsAg level in HBeAg‐negative patients with a viral load >10 5 copies/mL was significantly higher than in those with negative DNA . In this study, HBsAg/DNA ratio was higher in patients with low HBV DNA than in those with higher HBV DNA, similar to a study of 87 Senegalese CHB patients (75% with genotype E) . This reflects a disconnection between HBsAg production and HBV DNA replication and may be linked with higher frequency of mutation in the precore region.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This is in concordance with a Turkish study, which demonstrated that mean qHBsAg level in HBeAg‐negative patients with a viral load >10 5 copies/mL was significantly higher than in those with negative DNA . In this study, HBsAg/DNA ratio was higher in patients with low HBV DNA than in those with higher HBV DNA, similar to a study of 87 Senegalese CHB patients (75% with genotype E) . This reflects a disconnection between HBsAg production and HBV DNA replication and may be linked with higher frequency of mutation in the precore region.…”
Section: Discussionsupporting
confidence: 57%
“…We do not have a detailed mutational analysis of the precore region for our cohort, but reports from small studies suggest that mutation may affect HBsAg levels . The impact of changes in the precore region on HBV replication in genotype E patients was demonstrated in two genotype E exclusive studies and one mixed genotype study …”
Section: Discussionmentioning
confidence: 99%
“…However, in developing countries endemic for HBV (18), robust, cheaper, and easy-to-perform markers are essential in the management and monitoring of HBV patients (19). Hepatitis B viral load measurement is rarely accessible and where available often done once, which may not reflect real viral activity (19). tectable HBV DNA levels is still missing (20).…”
Section: Discussionmentioning
confidence: 99%
“…Genotype D is prevalent in Turkey, although we have not analyzed the HBV genotype of our case [19]. HBs Ag seroclearance is very rarely seen as an annual rate of 2.4-3.2% with Peg-IFN treatment, and only <1% with nucleoside/nucleotide analogues [20]. Therefore, we have not expected a HBs Ag seroclearance in our case.…”
Section: Discussionmentioning
confidence: 93%